ILMU MENURUT NURCHOLISH MADJID DALAM PRESPEKTIF POSTMODERNISME JEAN FRANCOIS LYOTARD - Amiruddin, Muhammad (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2018)
AbstractIt is a necessity that life is always developing and among its supports is science. That way, whether or not a civilization is good or not, it can be assessed how society views science and treats it. Today our world is entering what thinkers call postmodern, a century very different from before, so it cannot be denied or has influenced the rules of the game in various fields. Jean Francois Lyotard is one of the thinkers who talk about postmodern, especially his analysis of the field of science which has been organized differently by society today. Initially, science existed only as something to help human life, but in postmodern science it is now found that science is a tool of power with all interests and oppresses humanity; totalitarian and domination. That fact then, Lyotard attempted to transmit the concept to disrupt established science, by celebrating diversity. Islam really appreciates science, there is even a tendency that law is compulsory for Muslims. One of the Indonesian Islamic thinkers who in several of his writings discusses science is Nurcholish Madjid. Efforts to find out how Islam views science, feel the need to research it. Based on Lyotard's postmodern analysis tools, it is found that Islam can be a driving force for postmodern science or scientific performance.